(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2019)
There is an increasing interest in exploring the use of social media in the workplace, where the issue of the effect of this phenomenon often provokes opposite reactions. Consequently, managers face the challenge of making the right decision, allowing or limiting the use of social media. It is necessary for contemporary companies to create an environment that will enhance the performance of their employees, but also to understand the challenges and opportunities of the changing nature of the today’s workforce in the context of the development of new technologies and especially of social media. Thus, this paper draws on Uses and Gratification theory and aims to offer the theoretical model that explains the role and impact of different types of social media use at the workplace on employee’s innovative behaviour and individual work performance. The research model predicts that social media influences innovative work behaviour and individual work performance. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.